Properties of cotton yarns after oxidation of potassium permanganate in an acidic environment - Mirjana Kostić; Biljana Dojčinović (Zaštita Materijala)
The impact of nonselective cellulose oxidation (cotton fibre) by potassium permanganate in acidic environment, with or without additional treatment by sodium metabisulfite, on change of sorption (silver ions sorption), and deposition of manganese (IV) oxide were aims of this work. The standard methods and methods developed at Department of Textile Engineering of Faculty of Technology and Metallurgy Belgrade, were used for determination of introduced functional groups, sorption and mechanical properties of selected fibres. Inductively coupled plasma optical emission spectrometry ICP-OES was used for determination of manganese(IV) oxide deposited on cotton fibres. The changes of studied properties of cotton fibres were followed as a function of concentration and pH of the solution of oxidizing agent. Results obtained in this work showed that oxidized cotton fibre with improved sorption properties is appropriate as an initial raw for a wide range of textile products of special assignment.